Kyrgyz Republic country gender assessment. ([Manila] Asian Development Bank, 2019)
ADB initiates CGAs to map key gender equality issues, focusing on sectors supported by ADB funding. This is the second CGA for the Kyrgyz Republic, following the first one published in 2005. Providing key recommendations for future planning in different sectors, it can be of primary interest to development partners designing or undertaking projects in the Kyrgyz Republic and the Central Asia region.
Keywords: Gender equality -- sian Development Bank; Electronic books